Association of Coffee Consumption With Atrial Fibrillation Risk: An Updated Dose–Response Meta-Analysis of Prospective Studies - Cao, Yalin; Liu, Xiao; Xue, Zhengbiao; Yin, Kang; Ma, Jianyong; Zhu, Wengen; Liu, Fuwei; Luo, Jun; Sun, Junyi (Frontiers in Cardiovascular Medicine, 2022)
Background: Several published studies have examined the association of coffee consumption with atrial fibrillation (AF) risk, but their findings are still controversial. Therefore, we performed a systematic review and dose-response meta-analysis of prospective studies to determine the relationship between coffee consumption and the risk of incident AF. Methods: We systematically retrieved the Pubmed and Embase databases until October 2021 for pertinent studies that reported the association of coffee consumption (caffeinated or decaffeinated coffee) with AF risk. A cubic spline random-effects model was used to fit the potential dose-response curve. The effect estimates were expressed as adjusted risk ratios (RRs) and 95% confidence intervals (CIs). Results: A total of 10 prospective studies (11 cohorts) involving 30,169 AF events and 723,825 participants were included. In the dose-response analysis, there was a linear inverse association between coffee intake and risk of AF although not statistically significant (Pnon-linearity=0.25). Compared with participants with no coffee consumption, the RRs of AF risk estimated directly from the dose-response curve were 1.01 (95% CI 0.98–1.03) for 1 cup of coffee per day, 1.00 (0.97–1.04) for 2 cups per day, 0.99 (0.92–1.02) for 3 cups per day, 0.95 (0.89–1.01) for 4 cups per day, 0.94 (0.87–1.01) for 5 cups per day, 0.89 (0.79–1.02) for 6 cups per day, and 0.87 (0.76-1.02) for 7 cups per day. Per cup/day increase in coffee consumption was associated with a 2% reduced risk of AF (RR=0.98, 95% CI: 0.97–1.00, P=0.02). Conclusions: Our evidence of this meta-analysis suggested that coffee consumption had a trend in reducing the risk of AF in a dose-response manner. Further study could be conducted to reinforce our findings.